The roles of internal and external hydrogen in the deformation and fracture processes at the fatigue crack tip zone of metastable austenitic stainless steels. (December 2018) - Ogawa, Yuhei; Okazaki, Saburo; Takakuwa, Osamu; Matsunaga, Hisao
Abstract: Fatigue crack growth (FCG) tests were performed with two types of metastable austenitic stainless steels having different austenite phase stabilities under hydrogen-precharged conditions (internal hydrogen) and in gaseous hydrogen environments (external hydrogen). The materials showed a peculiarly slower FCG rate with internal hydrogen than with external hydrogen even though the hydrogen concentration was much higher under the internal hydrogen conditions. The results are interpreted in terms of hydrogen-modified plastic deformation character comprising inhibited cross-slipping or enhanced deformation twinning in combination with the sequence of hydrogen penetration and strain-induced α′ martensite formation in the local region surrounding the fatigue crack tip. Graphical abstract: Unlabelled Image